Finite-time dissipative control of uncertain singular T–S fuzzy time-varying delay systems subject to actuator saturation - Zhang, Jun; Liu, Deyou; Ma, Yuechao (Computational & applied mathematics, 2020)
This paper investigates the dissipative-based finite-time control for uncertain singular T–S fuzzy time-varying delay system affected by actuator saturation. First, the concept of dissipative stability and finite-time bound is presented. Then an appropriate Lyapunov–Krasovskii functional (LKF) is established and for the sake of reducing the conservatism of the results, some free matrices are introduced. Using the convexity property of the matrix inequality, some conditions are given to ensure the fuzzy system is finite-time bounded and dissipative. Moreover, by solving a series of linear matrix inequalities (LMIs), the controllers with the dissipative disturbance weakened level are derived. Finally, simulation examples are presented to show the feasibility and superiority of this method.